Low dietary intakes of essential nutrients during pregnancy in Vietnam - Nguyen, C.; Van Hoang, D.; Nguyen, P.; Van Ha, A.; Chu, T.; Pham, N.; Lee, A.; Van Duong, D.; Lee, Andy (MDPI Publishing, 2018)
Inadequate intake of nutrients during pregnancy has been associated with poor pregnancy and infant outcomes; however, evidence remains limited in low-resource settings in Asia. This paper assessed food, macronutrient, and micronutrient intakes among 1944 Vietnamese pregnant women. Dietary information was collected via an interviewer-administered food frequency questionnaire, and nutrient intakes were estimated using the Vietnamese food composition tables. The levels of nutrient intakes were evaluated against the Vietnamese recommended nutrient intakes (RNI) for pregnancy. The diet profiles were reported as means and percentages. The average daily food intakes across socio-demographic factors were compared using ANOVA, with adjustment for multiple comparisons by the Tukey–Kramer test. Rice, fruits, and vegetables were the main food sources consumed. The mean energy intake was 2004 kcal/day with 15.9%, 31.8%, and 52.2% of energy deriving from proteins, fats, and carbohydrates, respectively. Just over half of the women did not meet the RNI for total energy intake. The intakes of essential micronutrients including folate, calcium, iron, and zinc were below the RNI, and almost all pregnant women failed to meet the recommendations for these micronutrients. The associations of maternal age, education, and pre-pregnancy body mass index with nutrient intakes varied across the nutrient subgroups. Targeted programs are needed to improve nutrient intakes in Vietnamese pregnant women.